PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENGATASI KESULITAN SISWA MEMBACA AL-QUR’AN DI SMA DARUL ULUM 3 UNGGULAN PETERONGAN JOMBANG - Nur Hikmah; Abdul Jalil; Ika Anggraheni (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
The role of Islamic religious education teachers in overcoming the difficulties of students reading the Qur'an has become a hot topic lately. in essence the role of Islamic religious education teachers is very important to train students' fluency in reading the Qur'an because there are many people who think schools with a religious background are fluent in reading the Qur'an. Therefore, the researcher would like to discuss the role of Islamic education teachers in overcoming the difficulties of students reading the Qur'an at Darul Ulum 3 High School Peterongan Jombang. procedure of data collection is done by using an observation method that observes the learning process of the Qur'an and to find out the difficulties experienced by students. Both interview methods were conducted with assistant pricipal curriculum, teacher, and students. Three documentation methods require a number of documents from informants to be used as a process of completing research results. In this study the teacher has performed his role in overcoming students who have difficulty reading the Qur'an. In overcoming students' difficulties in reading the Qur'an the teacher has a way that is by providing special training for students who have difficulty reading the Qur'an outside of class hours.